2021
DOI: 10.1002/ajum.12286
|View full text |Cite
|
Sign up to set email alerts
|

Portal Venous Pulsatility Index as a predictor of fibrosis in patients with non‐alcoholic fatty liver disease

Abstract: Introduction: Non-alcoholic fatty liver disease (NAFLD) is a growing public health issue. Non-invasive methods to assess the fibrosis stage are limited, and biopsy remains the gold standard. The objective of our study was to assess whether the portal venous pulsatility index (VPI) can be used as a predictor of high-risk NAFLD at a tertiary referral centre for liver transplantation. Methods: We retrospectively reviewed patients with biopsy-proved NAFLD who had undergone a liver ultrasound scan within 1 year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…However, a slight variation emerged in patients with NAFLD and significant fibrosis, as our results indicated a VPI of 0.27, which was slightly higher than the value reported by Baikpour et al Nevertheless, these variations were attributed to the relatively milder degree of liver fibrosis in the SF (+) group in our study, as the majority of patients had LSM of <12 kPa. In the same context, other studies have reported similar results to ours in relation to VPI of the SF (+) group, ranging from 0.20 to 0.26 [16,17,19,20]. These consistent measurements across studies underscore the reliability of VPI as an ultrasonographic parameter.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, a slight variation emerged in patients with NAFLD and significant fibrosis, as our results indicated a VPI of 0.27, which was slightly higher than the value reported by Baikpour et al Nevertheless, these variations were attributed to the relatively milder degree of liver fibrosis in the SF (+) group in our study, as the majority of patients had LSM of <12 kPa. In the same context, other studies have reported similar results to ours in relation to VPI of the SF (+) group, ranging from 0.20 to 0.26 [16,17,19,20]. These consistent measurements across studies underscore the reliability of VPI as an ultrasonographic parameter.…”
Section: Discussionsupporting
confidence: 87%
“…This finding was corroborated by a subsequent study conducted by Hamed et al, which also observed a lower VPI among patients with NAFLD and fibrosis stage F2 or greater [19]. Lu et al presented contrasting results, showing no significant differences in VPI across different fibrosis stages [20]. Therefore, the potential of VPI as a predictive marker for liver fibrosis remains controversial.…”
Section: Introductionmentioning
confidence: 68%